If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5y + 1 = 0 Reorder the terms: 1 + 2x + -5y = 0 Solving 1 + 2x + -5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 2x + -1 + -5y = 0 + -1 Reorder the terms: 1 + -1 + 2x + -5y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x + -5y = 0 + -1 2x + -5y = 0 + -1 Combine like terms: 0 + -1 = -1 2x + -5y = -1 Add '5y' to each side of the equation. 2x + -5y + 5y = -1 + 5y Combine like terms: -5y + 5y = 0 2x + 0 = -1 + 5y 2x = -1 + 5y Divide each side by '2'. x = -0.5 + 2.5y Simplifying x = -0.5 + 2.5y
| 9x+18=2x+16 | | 4(k-3)-6=4k-(3k-2) | | 2x+-6y=0 | | 7-r+4= | | 50x+45y=1500 | | 4-x/3=x | | 8x^5(-4x^6-9)= | | y/3-y/4=5 | | 2x+9-9=61-9 | | 2x+9-9=61 | | 3senx=-4cosx | | 2x+5-3(x-5)=1 | | 1/7000 | | 2x+7-7=67 | | y=16x+8 | | 6x-5/4=x | | 0.3x+x=130 | | 0.7x+x=255 | | 3x^2+14x-104=0 | | -11+2x=9-3x | | 6+2x=14-3x | | x-5/3-1=3 | | (-6x-3)+(3x-2)=-11 | | (b+11)(b-11)= | | 4y+6=54 | | 5x^2+4xy-y^2=0 | | x^2-30x+1=0 | | 2x-3y=44 | | 3x^2+2x=4-7x | | x^2+4mx+8-4m=0 | | (12x^2)= | | 4m^2=24 |